Karakteristik Performa Reproduksi Ternak Kelinci - Riska Faradila; Anna Lidiyawati; Binti Khopsoh; Tika Fitria; Nining Haryuni; Lestariningsih Lestariningsih (Faculty of Agriculture, Musamus University, 2021)
This study was conduced to determine the reproduction performance characteristics of rabbits in Ngelegok sub-district, Blitar district. The material used in this study was rabbits in 5 people's farms in Ngelegok sub-district, Blitar district. The method used in this research is interviews and surveys directly to the location of the rabbit farming business. The data collected are primary data derived from a survey of reproduction in livestock breeding rabbits as many as 5 people in the Ngelegok sub-district of Blitar district, then conducted direct interviews with breeders using a list of questions available on the sheet questionnaires. The results of the study showed that the first breeding male rabbits was at least 6 months old, while for female cattle the first mating age was at least 5 months. The litter size produced by each type of rabbit varies. Litter size between 4-12 rabbits per birth. S / C of each type of rabbits there is no difference, with 2 or 3 times a marriage, rabbits likely to experience a pregnancy. Lambing frequency rabbits around 4.5 to 6 times per year, while the distance mating rabbit for mating again at least 14 days and a maximum of 55 days. The conclusion that the reproduction performance of rabbits in the Ngelegok sub-district of Blitar District is good enough, but every kind of rabbits have different reproduction performance characteristics.